Predictors of non-adherence to antihypertensive medication in Kinshasa, Democratic Republic of Congo: a cross-sectional study. (December 2015) - Lulebo, Aimée; Mutombo, Paulin; Mapatano, Mala; Mafuta, Eric; Kayembe, Patrick; Ntumba, Lisa; Mayindu, Alain; Coppieters, Yves
Abstract Background Hypertension remains a public health challenge worldwide. In the Democratic Republic of Congo, its prevalence has increased in the past three decades. Higher prevalence of poor blood pressure control and an increasing number of reported cases of complications due to hypertension have also been observed. It is well established that non-adherence to antihypertensive medication contributes to poor control of blood pressure. The aim of this study is to measure non-adherence to antihypertensive medication and to identify its predictors. Methods A cross-sectional study was conducted at Kinshasa Primary Health-care network facilities from October to November 2013. A total of 395 hypertensive patients were included in the study. A structured interview was used to collect data. Adherence to medication was assessed using the Morisky Medication Scale. Covariates were defined according to the framework of the World Health Organization. Logistic regression was used to identify predictors of non-adherence. Results A total of 395 patients participated in this study. The prevalence of non-adherence to antihypertensive medication and blood pressure control was 54.2 % (95 % CI 47.3–61.8) and 15.6 % (95 % CI 12.1–20.0), respectively. Poor knowledge of complications of hypertension (OR = 2.4; 95 % CI 1.4–4.4), unavailability of antihypertensive drugs in the healthcare facilities (OR = 2.8; 95 % CI 1.4–5.5), lack of hypertensive patients education in the healthcare facilities (OR = 1.7; 95 % CI 1.1–2.7), prior experience of medication side effects (OR = 2.2; 95 % CI 1.4–3.3), uncontrolled blood pressure (OR = 2.0; 95 % CI 1.1–3.9), and taking non-prescribed medications (OR = 2.2; 95 % CI 1.2–3.8) were associated with non-adherence to antihypertensive medication. Conclusion This study identified predictors of non-adherence to antihypertensive medication. All predictors identified were modifiable. Interventional studies targeting these predictors for improving adherence are needed.